Peran Persepsi Individu Terhadap Asuransi dan Model Kepercayaan Kesehatan dalam Pengambilan Keputusan Menggunakan Asuransi Jiwa - Ida Ayu Gede Rat Praba Ari; Dewi Puri Astiti (Jurnal Psikologi Udayana, 2014)
The use of health insurance is highly related with a person’s life depending on the perception of an individual and health belief model they own. Perception and health belief model bear an important role in determining how a person percieve their future especially related to health and older age well-being. One alternative in promising older age well being and health is through health insurance. This research was aimed to determine the role of individual perception upon insurance and health belief model in decision making process using life insurance. The method of this research is using quantitative method. The subjects of this research were the individuals using life insurance. The total subject in this research is 90 whom were selected using cluster random sampling. For hypothesis, the data was analyzed using multiple regression. The result of multiple regression analysis in this study is 0.764. Relative contribution of perception variable is 98.38% and the health belief model variable is 1.61%. Effective contribution of perception variable is 57.45% and the health belief model variable is 0.94%. This results show that there is a relation between the role of individual perception upon insurance and health belief model in decision making process using life insurance. However, when the data was analyzed using partial correlation, only individual perception of insurance variable has a relation with decision making variable. Keyword : Perception, Health Belief Model, Life Insurance